Police Narraritivy in the Risk Society - Campbell, Elaine (The British journal of criminology, 2004)
Interest in textual-discursive1 forms of police practice has been boosted by Ericson's and Haggerty's influential thesis of the communication technologies' used by police organizations in the risk society'. However, the thesis harbours certain theoretical lacunae, which became apparent in the author's empirical study of police decision-making processes. In particular, although it is supposed that police narrativity is rendered redundant in the risk society', the study finds that it flourishes and persists, even when explicitly proscribed and discouraged by police managers. A critical discourse analysis of police narratives suggests caution in accepting the totalizing imagery of the risk society' and all that it implies about the withering away' of policing's traditional place in the governance of social relations and social conflicts